There's more to colour than meets the eye. - Cowey, A; Heywood, C (1995)
Patients with cerebral achromatopsia, a perceptual disorder caused by ventromedial occipital brain damage, can be completely unable to arrange colours in chromatic sequence and fail most conventional tests of colour blindness. A possible explanation for cerebral achromatopsia is that the colour-opponent parvocellular (P) channel has been selectively and totally destroyed at the level of visual cortex, leaving vision to be mediated by the broad-band magnocellular (M) channel. The persistence of normal occipital visually evoked potentials, and preserved sensitivity to isoluminant chromatic gratings indicates that if this hypothesis is correct the destruction must occur beyond the striate cortex. We have shown that an achromatopsic subject can detect chromatic borders and construct shape from colour, and that he can even perceive the apparent direction of motion of a phase shifted isoluminant chromatic grating where perceived direction depends on knowing the sign of the colour diffence, i.e., which colour is which in the stripes. This and other evidence suggests that perhaps only one part of the cortical P channel has been destroyed. Does the critical area involved in achromatopsia correspond to cortical area V4 of monkeys, often implicated in processing wavelength? When Visual Area 4 is totally ablated in monkeys they have only a mild colour discrimination impairment and easily solve the colour ordering and colour selection tasks that an achromatopsic patient finds impossible. However, monkeys with ventromedial damage rostral to Area V4 do perform like achromatopsic patients, suggesting that the role of V4 in the perception of colour is still unclear and that the colour area of the human brain does not correspond to area V4.